Pengaruh Motivasi, Modal Minimal, Pengetahuan Investasi dan Teknologi Informasi Terhadap Minat Berinvestasi Mahasiswa di Pasar Modal - Septian Heris Syaputra; Armiani; Sofiati Wardah (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
This research aims to determine the influence of investment motivation, minimum investment capital, investment knowledge and information technology on the investment interest of university students in the city of Mataram. This research is associative research with a quantitative approach. The population in this study were students who were members of the Investment Gallery in universities throughout Mataram City with a sample of 115 students. Data were analyzed using SPSS 23. The results of this study show that investment motivation (X1) has a positive and significant effect on investment interest, minimum investment capital (X2), investment knowledge (X3) and information technology (X4) have a positive and significant effect on students' investment interest. The results of this research also show that investment motivation, minimum investment capital, investment knowledge and information technology can influence students' investment interest by 74,5%, while the remaining 25,5% is influenced by other variables outside the regression model used in this research. The results of this research show that students' investment interest in Mataram city universities is quite good because currently students already have knowledge about investment and are aware of the importance of investment.